The Efficiency of Resveratrol on Adenomatous Polyposis Coli Gene in Mice Colorectal Cancer Treated with Azoxymethane - Khayoon, Hussein Ali; Kadhim, Dr. Falah Muosa (International Journal of Psychosocial Rehabilitation, 2020)
Colorectal cancer (CRC) is the third most common cancer and the fourth most common cause of cancer-related death. Most cases of CRC are detected in Western countries, with its incidence increasing year by year. The probability of suffering from colorectal cancer is about 4%–5% and the risk for developing CRC is associated with personal features or habits such as age, chronic disease history and lifestyle. 5-Fluorouracil (5-FU) is the most commonly used therapy and the conventional treatment for colorectal cancer. However, its toxicity to normal tissues is considered a major obstacle to successful cancer chemotherapy; thus, resveratrol is used in combination with 5-FU to reduce its toxicity. The goal of our study is to investigate the mechanisms underlying the effects of resveratrol alone and in combination with 5-FU in inhibiting experimentally induced colon cancer. Gene expression analysis showed seemed lower expression of APC (adenomatus polyposis coli) gene in ( +) control significantly difference between positive and negative control by given Azoxymethane and normal saline respectively, The mean expression levels of (-) control (n=6) and combination (Res. +5-FU) (n=6) mice in the colon, There are high statistically significant expression differences. Error bars represent the 95% confidence intervals.